Keanekaragaman Jenis Orchidaceae (Anggrek-anggrekan)Di Kawasan Hutan Lindung Gunung Talang Sumatera Barat - Febry Fihendra Musa; - Syamsuardi; Ardinis Arbain (Universitas Andalas, 2013)
Taxonomical study of Orchidaceae at Talang Mountain had been done from September 2012 to March 2013. Plant samples were collected along climbing path of Talang Mountain using survey method. Those samples were processed and identified at Herbarium of Andalas University (Herbarium ANDA) Padang. This study found 23 species of orchids which belong to 16 genera (i.e. Arundina, Bulbophyllum, Ceratostylis, Coelogyne, Chelonistele, Dendrobium, Dendrochilum, Eria, Hylophila, Liparis, Oberonia, Peristylus, Phaius, Pholidota, Sphatoglotis, and Trichoglottis). Fifteen species were ephyphytic and eights pecies were teresterial plant. One speciesof the orchids (Eria merapiensis Schltr.) is endemic in Sumatra.Keywords : orchidaceae, species, identification, Talang Mountain, endemic.